Priming of Pisum sativum seeds with stabilized Pluronic P85 nanomicelles: effects on seedling development and photosynthetic function - Krumova, S; Petrova, A; Koleva, D; Petrova, S; Stoichev, S; Petrova, N; Tsonev, T; Petrov, P; Velikova, V (Photosynthetica, 2023)
Natural and synthetic polymers are widely explored for improving seed germination and plant resistance to environmental constraints. Here, for the first time, we explore stabilized nanomicelles composed of the biocompatible triblock co-polymer Pluronic P85 (SPM) as a priming agent for Pisum sativum (var. RAN-1) seeds. We tested a wide concentration range of 0.04-30 g(SPM) L-1. Applying several structural and functional methods we revealed that the utilized nanomicelles can positively affect root length, without any negative effects on leaf anatomy and photosynthetic efficiency at 0.2 g L-1, while strong negative effects were recorded for 10 and 30 g(SPM) L-1 concerning root length, leaf histology, and photoprotection capability. Our data strongly suggest that SPM can safely be utilized for seed priming at specific concentrations and are suitable objects for further loading with plant growth regulators.
Keywords: leaf anatomy; garden pea; poloxamer; plant biometry; chlorophyll fluorescence; nanoparticles